2017
DOI: 10.1038/npp.2017.223
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Treatment with Guanfacine, an Alpha2 Adrenergic Agonist, on Dopaminergic Tone in Tobacco Smokers: An [11C]FLB457 PET Study

Abstract: Guanfacine, a noradrenergic alpha2a agonist, reduced tobacco smoking in a 4-week trial and in animal models has been shown to reduce cortical dopamine release, which is critically involved in the reinforcing effect of tobacco smoking. We measured amphetamine-induced extrastriatal dopamine release before and after treatment with guanfacine with [C]FLB457, a dopamine D/D receptor radiotracer, and positron emission tomography (PET). Sixteen tobacco smokers had one set of [C]FLB457 PET scans on the same day, one b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Supplementary Table 3 also includes more extensive methodological details, such as PET camera, number of males and females, modeling method, reference region, scan length and modeling notes. Asterisks indicate transporters Receptor/transporter Neurotransmitter Tracer Measure n Age References D 1 Dopamine [ 11 C]SCH23390 BP ND 13 (7) 33 ± 13 Kaller et al 58 D 2 Dopamine [ 11 C]FLB-457 BP ND 37 (20) 48.4 ± 16.9 Smith et al 59 , 60 D 2 Dopamine [ 11 C]FLB-457 BP ND 55 (29) 32.5 ± 9.7 Sandiego et al 59 63 DAT * Dopamine [ 123 I]-FP-CIT SUVR 174 (65) 61 ± 11 Dukart et al 64 NET * Norepinephrine [ 11 C]MRB BP ND 77 (27) 33.4 ± 9.2 Ding et al 65 68 5-HT 1A Serotonin [ 11 C]WAY-100635 BP ND 35 (17) 26.3 ± 5.2 Savli et al 69 5-HT 1B Serotonin [ 11 C]P943 BP ND 65 (16) 33.7 ± 9.7 Gallezot et al 70 – 76 5-HT 1B Serotonin [ 11 C]P943 BP ND 23...…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Table 3 also includes more extensive methodological details, such as PET camera, number of males and females, modeling method, reference region, scan length and modeling notes. Asterisks indicate transporters Receptor/transporter Neurotransmitter Tracer Measure n Age References D 1 Dopamine [ 11 C]SCH23390 BP ND 13 (7) 33 ± 13 Kaller et al 58 D 2 Dopamine [ 11 C]FLB-457 BP ND 37 (20) 48.4 ± 16.9 Smith et al 59 , 60 D 2 Dopamine [ 11 C]FLB-457 BP ND 55 (29) 32.5 ± 9.7 Sandiego et al 59 63 DAT * Dopamine [ 123 I]-FP-CIT SUVR 174 (65) 61 ± 11 Dukart et al 64 NET * Norepinephrine [ 11 C]MRB BP ND 77 (27) 33.4 ± 9.2 Ding et al 65 68 5-HT 1A Serotonin [ 11 C]WAY-100635 BP ND 35 (17) 26.3 ± 5.2 Savli et al 69 5-HT 1B Serotonin [ 11 C]P943 BP ND 65 (16) 33.7 ± 9.7 Gallezot et al 70 – 76 5-HT 1B Serotonin [ 11 C]P943 BP ND 23...…”
Section: Resultsmentioning
confidence: 99%
“…This analysis was conducted because, in a recent report, amphetamine-induced displacement of [ 11 C]FLB 457 BP ND was detected with SRTM, but not kinetic analyses (Sandiego et al, 2015). The inability to displace [ 11 C]FLB 457 BP ND in the cortex following an oral amphetamine challenge was unexpected, because three independent groups have replicated this observation in five different cohorts of healthy controls ( Table 5) (Narendran et al, 2009; Narendran et al, 2014; Sandiego et al, 2015; Sandiego et al, 2017; Slifstein et al, 2015). The scanning of subjects with [ 11 C]NPA before [ 11 C]FLB 457 in the amphetamine PET studies allowed for us to contrast ΔBP ND in the striatum with that in the cortex.…”
Section: Discussionmentioning
confidence: 98%
“…This result also has implications for longitudinal studies that have used [ 11 C]FLB 457 and amphetamine to measure dopamine release on two different days. For example, a recent study that documented amphetamine-induced displacement of [ 11 C]FLB 457 before and after three weeks of guanfacine treatment reported that guanfacine led to a decrease in dopamine release (∆BP ND ) (Sandiego et al, 2017). However, the smaller ∆BP ND measured in the guanfacine-treated relative to the untreated condition was attributable to a non-significant 4–12% decrease in baseline (not post-amphetamine) BP ND after chronic guanfacine treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several brain positron emission tomography (PET) imaging studies have investigated DA release following an amphetamine (AMPH) challenge both in the striatum 4–8 and in the cortex 9–13 . Overall, these studies found that striatal DA signalling is related to positive rewarding effects, such as euphoria and drug wanting.…”
Section: Introductionmentioning
confidence: 99%